The Oxford handbook of assessment policy and practice in music education, Volume 2 - Brophy, Timothy S. 1952- (Oxford handbooks online, 2019)
In the music classroom, instructors who hope to receive aid are required to provide data on their classroom programs. Due to the lack of reliable, valid large-scale assessments of student achievement in music, however, music educators in schools that accept funds face a considerable challenge in finding a way to measure student learning in their classrooms. From Australia to Taiwan to the Netherlands, music teachers experience similar struggles in the quest for a definitive assessment resource that can be used by both music educators and researchers. In this two-volume Handbook, contributors from across the globe come together to provide an authority on the assessment, measurement, and evaluation of student learning in music. The Handbook's second volume offers a series of practical and US-focused approaches to music education assessment